PENGGUNAAN BAHASA DALAM PEMANFAATAN MEDIA BARU: PERSUASIVE LANGUAGE DI MEDIA SOSIAL DALAM MENINGKATKAN MINAT MENGUNJUNGI DESTINASI WISATA - Ronny Sugiantoro (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
In the current era of digitalization, the role of social media is very large in supporting product promotion, following online media. Especially in promoting tourist destinations, lately the role of social media is very large in influence. With persuasive, sometimes even provocative language, many tourist destinations have been boosted and become famous thanks to promotions through social media. So that people will also be educated to choose tourist destinations, from the many choices offered through social media. This paper intends to examine the extent to which the role and influence of media language, especially social media (social media) in promoting tourist destinations. The hope is that specific language style formulations for the media, especially social media, can be found in supporting the promotion of tourist destinations.Keywords: Ttourist Destinations; Social Media; Persuasive Language.